CEMC Banner

Problem of the Month
Solution to Problem 4: January 2023

  1. Since a and b are positive integers and c is larger than both of them, the smallest value that c can take is c=2. The possible values of c are therefore c=2, c=3, and so on up to c=n+1.

    The only triple in S with the property that c=2 is (1,1,2), so there is one triple with c=2. The triples in S with c=3 are (1,1,3), (1,2,3), (2,1,3), and (2,2,3), so there are four triples with c=3.

    In general, if c=r, then a and b can both be any integer from 1 through r1 inclusive. Thus, there are (r1)×(r1)=(r1)2 triples in S with c=r. Since r ranges from 2 through n+1, there are exactly 12+22+32+42++(n1)2+n2=p2(n) triples in S.

  2. We will now count the triples in S by considering them according to the number of distinct integers that occur in the triple. For example, there are two distinct integers in (1,1,2) and three distinct integers in (1,5,7).

    If (a,b,c) is in S, then there are at most three distinct integers in the triple (since there are only three integers in total). As well, since a<c, the integers cannot all be equal. Therefore, there are either two distinct integers or three distinct integers in (a,b,c).

    Suppose x, y, and z are three distinct integers between 1 and n+1 inclusive. Since they are distinct, one of them is the largest. Assuming z is the largest, the triples (x,y,z) and (y,x,z) are both in S, and these are the only triples in S that contain the integers x, y, and z. Therefore, for every way to choose three distinct integers between 1 and n+1 inclusive, there are two triples in S. This observation means there are 2(n+13) triples in S with three distinct integers in them.

    Now suppose that x and y are two distinct integers with x<y. Then the only triple in S that contains exactly the integers x and y is (x,x,y). Thus, for every two distinct integers between 1 and n+1 inclusive, there is exactly one triple in S that contains exactly those two integers. Therefore, there are (n+12) triples in S with two distinct integers in them.

    Therefore, the number of elements in S is (n+12)+2(n+13).

    From part (a), p2(n)=(n+12)+2(n+13)=(n+1)!2!(n1)!+2(n+1)!3!(n2)!=(n+1)n2+2(n+1)n(n1)6=n(n+1)(12+n13)=n(n+1)(36+2(n1)6)=n(n+1)(3+2n2)6=n(n+1)(2n+1)6

  3. Fix a positive integer n. Using the idea from parts (a) and (b), we let Sk be the set of ordered lists of k+1 positive integers (x1,x2,x3,,xk,xk+1) with the property that each integer xi is between 1 and n+1 inclusive and xk+1 is larger than every other integer in the list. A list of the form (x1,x2,x3,,xk,xk+1) is called a (k+1)-tuple.

    As in the case with k=2, it is not possible for a (k+1)-tuple in Sk to have xk+1=1. This is because the other integers are positive and xk+1 must be the largest integer in the list (it cannot be "tied" for the largest). The possible values of xk+1 are 2 through n+1.

    For a fixed value of xk+1, say xk+1=r, if (x1,x2,x3,,xk,xk+1) is in Sk, then x1 through xk can each be any positive integer less than r, of which there are r1. Therefore, the number of (k+1)-tuples in Sk with xk+1=r is (r1)2. The possible values of r are 2 through n+1, so we have that the number of elements in Sk is 1k+2k+3k++(n1)k+nk=pk(n)

    Following the reasoning of part (b), we now want to count the elements in Sk a different way. Since xk+1 is the largest integer in the (k+1)-tuple, there are at least two distinct integers in every (k+1)-tuple in Sk. As well, there are at most k+1 distinct integers in every (k+1)-tuple. Suppose we have chosen r distinct positive integers between 1 and n+1 inclusive with 2rk+1. We would like to count the (k+1)-tuples in Sk that contain exactly those r integers. For example, suppose k=4 and r=3. We need to count the number of 5-tuples that use exactly three given integers with the largest integer occurring only in the rightmost position. Suppose the largest integer is C and the other two are A and B. The 5-tuples in Sk are

    (A,A,A,B,C), (A,A,B,A,C), (A,B,A,A,C), (B,A,A,A,C), (B,B,B,A,C), (B,B,A,B,C), (B,A,B,B,C), (A,B,B,B,C), (A,A,B,B,C), (A,B,A,B,C), (A,B,B,A,C), (B,A,A,B,C), (B,A,B,A,C), (B,B,A,A,C)

    and so there are 14 5-tuples in Sk with exactly those three integers. This means that there are 14(n+13) 5-tuples in Sk that have exactly three distinct integers in them. The important thing to notice here is that the constant 14 does not depend on n. We could do a similar count to see how many 9-tuples there are in S8 with exactly five distinct integers. The combinatorics might be a bit tedious, but in the end, we would find that the number of 9-tuples in S8 with exactly five distinct integers is some multiple of (n+15) where the multiplier does not depend on n.

    Putting this together, there must be some constants a2,,ak+1 so that pk(n)=a2(n+12)+a3(n+13)++ak(n+1k)+ak+1(n+1k+1) where each coefficient ar is equal to the number of (k+1)-tuples in Sk that contain exactly a fixed set of r distinct integers.

    Put differently, suppose R is a set of r distinct positive integers. Then ar is the number of (k+1)-tuples that satisfy the following three conditions: every integer in the (k+1)-tuple comes from R, every integer in R occurs at least once in the (k+1)-tuple, and the largest integer in R occurs exactly once and is in the rightmost position.

    Before moving on, we make one final observation. With the convention that (uv)=0 when u<v, the equation above makes sense even when n+1 is smaller than the bottom number in the binomial coefficient. For example, if k=5 and n=2, then the term a4(n+14)=a4(34) is counting the number of 6-tuples consisting of four distinct integers between 1 and n+1=3 inclusive. There is no way to choose four distinct integers from the list 1, 2, 3, so there should be zero such 6-tuples, and the fact that (34)=0 records this observation.

  4. From part (c), we have that p3(n)=a2(n+12)+a3(n+13)+a4(n+14) for some constants a2, a3, and a4. Using that p3(1)=13=1, we have that 1=p3(1)=a2(1+12)+a3(1+13)+a4(1+14)=a2(22)+a3(23)+a4(24)=a2+0+0 and so a2=1. With n=2, we have p3(2)=13+23=9, so 9=p2(2)=(2+12)+a3(2+13)+a4(2+14)=(32)+a3(33)+a4(34)=3+a3+0 and so a3=6. Finally, using n=3, we have p3(3)=13+23+33=36, so 36=p3(3)=(42)+6(43)+a4(44)=6+6×4+a4 from which it follows that a4=6. Recall that a4 is equal to the number of four-tuples in S3 consisting of a fixed set of four distinct integers. Indeed, the largest integer must go in the rightmost position, and there are 6 ways to arrange the other three integers, so a4=6 makes sense from a combinatorial perspective.

    We now have shown that p3(n)=(n+12)+6(n+13)+6(n+14)=(n+1)n2+6(n+1)n(n1)6+6(n+1)n(n1)(n2)24 and after some simplification, we get that p3(n)=n2(n+1)24

    We can approach p4(n) similar to how p3(n) was approached above. We start with p4(n)=a2(n+12)+a3(n+13)+a4(n+14)+a5(n+15) and then use that p4(1)=1, p4(2)=14+24=17, p4(3)=14+24+34=98, and p4(4)=14+24+34+44=354 to solve for a2, a3, a4, and a5. After doing this, we find that a2=1, a3=14, a4=36, and a5=24. Therefore, after some simplification, we get

    p4(n)=(n+12)+14(n+13)+36(n+14)+24(n+15)=n(n+1)(2n+1)(3n2+3n1)30

  5. Using that p5(n)=c0+c1n+c2n2+c3n3+c4n4+c5n5+c6n6, we can find a general expression for p5(n)p5(n1). n5=p5(n)p5(n1)=c0+c1n+c2n2+c3n3+c4n4+c5n5+c6n6(c0+c1(n1)+c2(n1)2+c3(n1)3+c4(n1)4+c5(n1)5+c6(n1)6)=c0+c1n+c2n2+c3n3+c4n4+c5n5+c6n6c0c1(n1)c2(n22n+1)c3(n33n2+3n1)c4(n44n3+6n24n+1)c5(n55n4+10n310n2+5n1)c6(n66n5+15n420n3+15n26n+1) and after collecting like terms, we get n5=(c1c2+c3c4+c5c6)+(2c23c3+4c45c5+6c6)n+(3c36c4+10c515c6)n2+(4c410c5+20c6)n3+(5c515c6)n4+6c6n5 We can now equate coefficients to get the system of equations 6c6=15c515c6=04c410c5+20c6=03c36c4+10c515c6=02c23c3+4c45c5+6c6=0c1c2+c3c4+c5c6=0 From the first equation, we get c6=16. Substituting this into the second equation gives 5c515×16=0 so c5=12. Continuing this way, we get that c4=512, c3=0, c2=112, and c1=0. Therefore p5(n)=c0112n2+512n4+12n5+16n6 To solve for c0, we can use that p5(1)=1 to get the equation 1=c0112+512+12+16=c0+1 which means c0=0. Finally, we can rearrange p5(n) into a nicer form p5(n)=112n2+512n4+12n5+16n6=n2+5n4+6n5+2n612=n2(n+1)2(2n2+2n1)12

  6. Fix a positive integer k and consider the function pk(n). We observed earlier that pk(n) is a polynomial in n. While pk(n) is designed to output 1k+2k++nk when n is a positive integer, there is nothing to stop us from "symbolically" evaluating pk(n) when n is not an integer. For example, even though p1(14) does not have the same meaning as p1(n) when n is a positive integer (we cannot "add together the first 14 positive integers"), we can still substitute 14 into the formula for p1 to get p1(14)=14×542=532.

    Now consider the function fk(n)=pk(n)pk(n1)nk where n is allowed to be any real number. The function fk(n) is the sum/difference of three polynomials, so it is itself a polynomial. Since pk(n)pk(n1)=nk for all positive integers n, n is a root of fk(n) for all positive integers n. By the fact in the hint, a polynomial with infinitely many roots must be the constant zero function, so pk(n)pk(n1)nk=0 for all real numbers n.

    With n=1, we get that pk(1)pk(0)=1k=1, but since pk(1)=1, we have that 1pk(0)=1, so pk(0)=0. Similarly, by considering n=0, we get that pk(0)pk(1)=0k, and since pk(0)=0, we have 0pk(1)=0, so pk(1)=0 as well. We have shown that 0 and 1 are roots of the polynomial pk(n), which shows that n and n+1 are factors of pk(n). This means n(n+1) is a factor of pk(n).

    We now suppose that k is even, which means nk=(n)k for all real numbers n. From above, we have that pk(0)=pk(1)=0. Considering pk(n)pk(n1)=nk at n=1, we have that pk(1)pk(2)=(1)k, and since k is even and pk(1)=0, we have pk(2)=1k or pk(2)=1k.

    Next, we use pk(n)pk(n1)=nk with n=2 to get pk(2)pk(3)=(2)k=2k, and since pk(2)=1k, this means pk(3)=1k+2k or pk(3)=(1k+2k).

    Continuing this way, we have pk(3)pk(4)=(3)k=3k, so 1k2kpk(4)=3k, and so pk(4)=(1k+2k+3k). We have now shown that pk(n)=pk(n1) for the positive integers n=0, n=1, n=2, n=3, and n=4. This pattern continues. It can be proven using mathematical induction that pk(n)=pk(n1) for all positive integers n.

    This means that pk(n)+pk(n1)=0 for every non-negative integer. Therefore, the polynomial pk(n)+pk(n1) has infinitely many roots, and so must be equal to 0 for every real number n.

    Taking n=12, we get pk(12)+pk(121)=0 which simplifies to 2pk(12)=0. Therefore, 12 is a root of pk(n) when k is even. Thus, pk(n) has a factor of n+12, which is equivalent to having a factor of 2n+1=2(n+12).